Changes in body composition and athletic performance in National Collegiate Athletic Association Division I female field hockey athletes throughout a competitive season - Summer, L. C.; Cheng, R.; Moran, J. T.; Lee, M.; Belanger, A. J.; Taylor, W. L.; Gardner, E. C. (The Journal of Strength and Conditioning Research, 2024)
The purposes of this study were (a) to analyze the changes in total and regional body composition measurements in a National Collegiate Athletic Association (NCAA) Division I female field hockey team throughout a 17-game competitive season using dual X-ray absorptiometry (DXA); (b) to examine improvements, if any, in athletic performance measures after a season; and (c) to report on the relationship between these body composition changes and changes in athletic performance. Preseason and postseason dual-energy DXA and performance data from the 2019-2020 season were retrospectively identified for 20 field players (forwards, midfielders, and defenders). Body composition data included total and regional fat mass, lean mass, and body fat percentage, whereas athletic performance measures included the vertical jump, 10-yard dash, and pro-agility (5-10-5) shuttle run. All variables were quantitative and analyzed using paired t-tests or its nonparametric equivalent and an alpha level of p < 0.05 was used to determine significance. After a competitive season, athletes had significant decreases in fat mass and increases in lean mass in their arms, legs, trunks, gynoids, and total body measurements. Android fat mass and body fat percentage also decreased. Athletes performed significantly better on the pro-agility shuttle run at the end of the season, but no significant differences were observed in other performance metrics. Moderate correlations were observed between changes in body composition (total fat mass and total lean mass) and changes in athletic performance. Our study provides a novel, longitudinal assessment of body composition and athletic performance for elite female field hockey athletes that will help trainers and coaches better understand how these variables change throughout a season and allow them to better prepare their players for competitive success.